2003
DOI: 10.1152/japplphysiol.00472.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impaired leg vasodilation during dynamic exercise in healthy older women

Abstract: The purpose of the present study was to test the hypothesis that leg blood flow responses during leg cycle ergometry are reduced with age in healthy non-estrogen-replaced women. Thirteen younger (20-27 yr) and thirteen older (61-71 yr) normotensive, non-endurance-trained women performed both graded and constant-load bouts of leg cycling at the same absolute exercise intensities. Leg blood flow (femoral vein thermodilution), mean arterial pressure (MAP; radial artery), mean femoral venous pressure, cardiac outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 23 publications
6
37
0
1
Order By: Relevance
“…In contrast, some studies have found no difference between Q & m to exercising limbs in young and old subjects (Jasperse et al, 1994;Olive et al, 2002;Proctor et al, 2003b). However, the current literature is certainly not definitive on this issue (Wahren et al, 1974;Proctor et al, 1998;Proctor et al, 2003a) with differences possibly related to the activity level of the population studied, the function of the active muscle(s), and/or the intensity of the exercise. More importantly, recent evidence has established that large artery and limb blood flow may not be an appropriate analog of regional microvascular flow Harper et al, 2006) which may explain the disparity between studies that have measured bulk arterial flow as distinct from microcirculatory flow (present results; Hammer & Boegehold, 2005).…”
Section: Comparisons To Previous Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, some studies have found no difference between Q & m to exercising limbs in young and old subjects (Jasperse et al, 1994;Olive et al, 2002;Proctor et al, 2003b). However, the current literature is certainly not definitive on this issue (Wahren et al, 1974;Proctor et al, 1998;Proctor et al, 2003a) with differences possibly related to the activity level of the population studied, the function of the active muscle(s), and/or the intensity of the exercise. More importantly, recent evidence has established that large artery and limb blood flow may not be an appropriate analog of regional microvascular flow Harper et al, 2006) which may explain the disparity between studies that have measured bulk arterial flow as distinct from microcirculatory flow (present results; Hammer & Boegehold, 2005).…”
Section: Comparisons To Previous Researchmentioning
confidence: 93%
“…For example, several studies have reported Q & m reductions when comparing old rats to their younger counterparts during electrical stimulation of skeletal muscle (Irion et al, 1987;Hammer & Boegehold, 2005). Similarly, in humans, Q & m to the active leg muscles is reduced during dynamic exercise in older men (Wahren et al, 1974;Proctor et al, 1998) and women (Proctor et al, 2003a). Recently, Donato et al demonstrated that the difference in the leg Q & m response to exercise found between young and old subjects was a product of the response to the exercise stimulus itself, as opposed to variations in resting Q & m between age groups.…”
Section: Aging-induced Alterations In Exercise Hyperemiamentioning
confidence: 99%
“…An inability to augment cardiac output during exercise has been functionally linked to the reduced exercise tolerance with aging (1, 23, 36, 53). A blunted skeletal muscle blood flow response to dynamic exercise has also been reported in older humans and animals (1,33,37,47,48,50). However, other studies have documented preserved skeletal muscle blood flow during exercise in aged humans (38,40,44,49).…”
mentioning
confidence: 86%
“…blood flow; aging; muscle contractions THE REGULATION OF BLOOD FLOW and oxygen delivery to contracting muscle is a complex response that involves mechanical factors, the sympathetic nervous system, and local metabolic and endothelium-derived substances that can influence vascular tone (28). In aging humans, an imbalance occurs in these regulatory mechanisms that typically results in impaired vasodilation and attenuated muscle blood flow during exercise (17,19,25,26). Investigators have hypothesized that impaired endothelial vasodilator function contributes to the age-related impairment in muscle blood flow during exercise (8,27).…”
mentioning
confidence: 99%